Working capital management: a research in the furniture Divinópolis, MG microenterprises (Research, Society and Development, 2018)
The microenterprises are essential for brazilian economy due to their capacity to generate jobs and income. However, a large part of them close their business early. Lack of working capital and management failure are among the reasons. Considering the importance of an efficient working capital management for survival of these companies, the general goal of this work was identifying and analyzing the main difficulties of furniture companies in Divinópolis, Minas Gerais, regarding working capital management. This is a descriptive research with qualitative and quantitative approach. The data were collected by a quiz answered by fifteen furniture companies in Divinópolis, MG. It was concluded that the main difficulties on short term financial resources management, according to the view of the financial managers who answered the research, were making daily cash flow control, knowing the profit of each work done, separate the finances of the business and the owners, knowing the cost of each work and knowing the value of product stock. These issues were attributed to the fact of the financial managers haven’t studied finances and because they had other responsibilities, besides the financial management.